(untitled) (Research, Society and Development, 2021)
Objective: To describe the path of the Faculty of Dentistry at Federal University of Minas Gerais (FAO-UFMG) in the creation, regulation, accreditation and maintenance of the Academic Leagues of the unit. Methodology: publications and actions of Academic Leagues of the FAO-UFMG from the first half of 2018 to February 2021 were analyzed, correlating the data to the history of creation of these leagues. Results: participation in scientific events, institutional videos, Instagram posts for the community, dialogued and magisterial expository classes open to the academic community were found. Conclusion: The dialogical relationship with society can only be observed in a moment. The COVID 19 pandemic imposed the issue of remote communication on the activities of the issue of remote communication on the activities of the Leagues, which may have jeopardized their performance. The Academic Leagues of FAO_UFMG, despite being incipient, demonstrate the ability to develop in the binding students, the capacity for self-management, taking advantage of the pro-activity, interest in learning and leadership on the part of the institution’s student body.